2018
DOI: 10.1111/scd.12266
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related concerns, behavior, and communication with health care providers of patients with breast cancer: impact of different treatments

Abstract: BCa treatments impact oral health. Low percentages of BCa patients had received specific information about impacts of BCa treatments on oral health from their dentists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
8
0
3
Order By: Relevance
“…Similarly, a recent study conducted in the USA reported 1.6 mouth sores on average among breast cancer patients. 26 In another study that collectively analyzed common cancer-related and treatment-related symptoms, including xerosto-mia and pain, the percentage of moderate to severe symptoms reported by breast cancer patients was consistently lower than those reported by colorectal and lung cancer patients as noted in our study. 27 Future studies could focus on identifying possible mechanisms that influenced better oral health experience in breast cancer patients.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, a recent study conducted in the USA reported 1.6 mouth sores on average among breast cancer patients. 26 In another study that collectively analyzed common cancer-related and treatment-related symptoms, including xerosto-mia and pain, the percentage of moderate to severe symptoms reported by breast cancer patients was consistently lower than those reported by colorectal and lung cancer patients as noted in our study. 27 Future studies could focus on identifying possible mechanisms that influenced better oral health experience in breast cancer patients.…”
Section: Discussionsupporting
confidence: 60%
“…Taichman LS et al 11 When comparing three groups of breast cancer patients to salivary flow, the aromatase inhibitor group was significantly more affected with xerostomia than the tamoxifen and chemotherapy groups. And when compared to breast cancer patients with those without diagnosis, xerostomia was 2.48 times more prevalent in the group with the disease (2.48 versus 1.70; p <0.01).…”
Section: Authors Resultsmentioning
confidence: 99%
“…performed sialometry with and without salivary stimulation, finding that hyposalivation was present in almost 30% of patients who complained of xerostomia. 11 As we can see, there is no specific method for the identification of xerostomia, since this sensation is subjective, but one should look for the most appropriate method for the studied population, as well as the appropriate time for its application.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between groups regarding the plaque and gingival index, and this can be related to the similarity of oral hygiene habits of the participants. In contrast, some studies concluded that women receiving antiestrogen therapy may experience greater levels of depression, musculoskeletal symptoms, and fatigue and that these may prevent them from maintaining optimal oral hygiene 31,32 . Stress and fatigue levels of patients have not been evaluated within the limitations of our study, but the increase in PI values of individuals who have been using AI for more than 2 years may be related to this situation.…”
Section: Discussionmentioning
confidence: 73%